URBAN SPRAWL AND RESIDENTIAL DEVELOPMENT IN THE ROMANIAN METROPOLITAN AREAS - NICOLETA TICANĂ; INES GRIGORESCU; BIANCA MITRICĂ; IRENA MOCANU (Revue Roumaine de Géographie)
In Romania nearly 7,500,000 (34%) inhabitants are living in metropolitan areas. The socio-economic and political changes brought about by the post-communist period have reshaped the metropolitan landscape together with its functional and socio-spatial pattern triggering a wide range of transformations mainly related to urbansprawl process (suburbanization). As one of its major consequences, residential development had caused the deconcentration and the spatial redistribution of the population within metropolitan areas. The paper attempts to analyse the main suburbanization-related residential patterns in connection with their key driving forces(socio-political, demographic, economic, housing) and the associated environmental consequences in the Romanian metropolitan areas in terms of: urban (residential) sprawl, real-estate market dynamics, changes in spatial pattern of population, living floor dynamics, etc., with a special focus on the most significant metropolitan systems: Bucharest, Oradea, Iaşi and Constanţa. The present study will combine GIS computer mapping techniques with housing and demographic data and field surveys to identify the main urban-sprawl-related current residential patterns in the Romanian metropolitan areas and understand causes of change in order to predict how alternative policies will influence future spatial development.